Cloning and analysis of the Eg4CL1 gene and its promoter from oil palm (Elaeis guineensis Jacq.) - Chong, Yusuf Yu Lok; Idris Abu Seman,; Nor Aini Ab Shukor,; Mohd Norfaizull Mohd Nor,; Mohd Puad Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The empty fruit bunches of oil palm have been used as the raw material to produce biofuel. However, the lignin present in oil palm tissues hampers the enzymatic saccharification of lignocellulosic biomass and lower the yield of biofuel produced. Hence, various efforts were taken to identify the lignin biosynthetic genes in oil palm and to investigate their regulation at the molecular level. In this study, a lignin biosynthetic gene, Eg4CL1 and its promoter were isolated from the oil palm. Eg4CL1 contains the acyl-activating enzyme consensus motif and boxes I & II which are present in other 4CL homologs. Eg4CL1 was clustered together with known type I 4CL proteins involved in lignin biosynthesis in other plants. Gene expression analysis showed that Eg4CL1 was expressed abundantly in different organs of oil palm throughout the course of development, reflecting its involvement in lignin biosynthesis in different organs at all stages of growth. The presence of the lignification toolbox - AC elements in the 1.5 kb promoter of Eg4CL1 further suggests the potential role of the gene in lignin biosynthesis in oil palm. Together, these results suggested that Eg4CL1 is a potential candidate gene involved in lignin biosynthesis in oil palm.